2022
DOI: 10.1177/17449871211058854
|View full text |Cite
|
Sign up to set email alerts
|

The history of disaster nursing: from Nightingale to nursing in the 21st century

Abstract: Background Nurses have a rich history in performing their duty both domestically and internationally in response to a disaster. Comprising the largest proportion of the healthcare workforce, nurses possess a unique opportunity to inform disaster planning and management. With the ongoing threat from COVID-19 and continuing conflict, humanitarian aid needs, epidemics and natural disasters; the capacity of nurses to continue to respond in times of global need is unparalleled. Aims The aim of this paper is to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…By using the lens of Tronto's framework of ethical care we are able to distinctly examine and report on the micro (personal), meso (care‐home) and macro national polices and public discourses in relation to attentiveness and responsibility to provide good care and the consequences of when this was not possible; the demand and willingness to extend professional competencies; the responsiveness of relatives and care regulators to care provision and the way in which the care‐home workforce worked together. We now explore each component drawing on literature to situate our discussion in a registered nurses' professional sense of duty, obligation, and responsibility (Fletcher et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By using the lens of Tronto's framework of ethical care we are able to distinctly examine and report on the micro (personal), meso (care‐home) and macro national polices and public discourses in relation to attentiveness and responsibility to provide good care and the consequences of when this was not possible; the demand and willingness to extend professional competencies; the responsiveness of relatives and care regulators to care provision and the way in which the care‐home workforce worked together. We now explore each component drawing on literature to situate our discussion in a registered nurses' professional sense of duty, obligation, and responsibility (Fletcher et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to reduce barriers to disaster planning for patients are needed (Bell et al, 2021). Fletcher et al (2022) call for a need to better understand the influence and role of nurses in policy development, strategic and operation response, workforce preparation, and education development. Additionally, they suggest more research on role profiles within the four phases of disaster response.…”
Section: Future Researchmentioning
confidence: 99%
“…Emergency management and disaster response have historically been more reactive than proactive, although a shift to prevention, planning, and risk reduction has emerged over the past 20 years. The literature focuses heavily on the preparedness and response phases and less on the clinician's role in the mitigation and recovery phases (Fletcher et al, 2022). The COVID-19 pandemic revealed a need for ongoing training, education, research, and planning to mitigate negative consequences on healthcare providers, patients, and communities (Anderson & Beach, 2022; Bell et al, 2022; Elliott et al, 2023).…”
mentioning
confidence: 99%
“…Calamassi et al (2021) explored the experiences of healthcare professionals during the conflict in Iraq. This study identified themes that in some regards are somewhat unique to the setting, but others that may also be recognisable in other healthcare settings; a second paper by Fletcher et al (2022) utilises a historical interpretative approach and explores the history of disaster nursing from the time of Florence Nightingale to the present day, highlighting the dynamic nature of nursing in these circumstances and how nurses must have strategic and policy-level input to plan for future events.…”
Section: Adaptability Innovation and Resiliencementioning
confidence: 99%